Semi-industrial continuous band microwave dryer for energy and exergy analyses, mathematical modeling of paddy drying and it's qualitative study. (1st November 2017) - Jafari, Hassan; Kalantari, Davood; Azadbakht, Mohsen
Abstract: The aims of this research are to investigate the energy and exergy analyses for continuous band microwave dryer and qualitative changes of the crop during drying. A semi-industrial continuous microwave dryer was fabricated. The penetration depth of microwave's waves, the percentage of grain breakage, mathematical modeling, effective moisture diffusivity, and specific energy consumption were obtained and energy and exergy analyses were done. The results showed that energy efficiency and exergy efficiency at the same powers increased by increasing the thickness of grain layers. In the same layers with increasing the microwave power, energy efficiency and exergy efficiency were reduced. In layers with the same thickness, increasing in power of microwave increased the specific energy consumption. The models of Wang and Page showed the best fit for layer 6 mm and the model of Lewis indicated best fit for layer 12 mm and for layer 18 mm, the model of Wang was considered as the best model. The breakage of the paddy grains was increased with increasing the rate of changes in moisture ratio and increased energy absorption. Finally, the power of 90 W and thickness of 18 mm for the layer of paddy is recommended. Highlights: Energy and exergy efficiency increased by increasing the thickness of grains. Energy absorption occurs in layers equal to the penetration depth of microwave. By increasing the thickness of the paddy, specific energy consumption reduced. The breakage percentage of grains were related to the absorption of microwave. Effective moisture diffusivity is related to the power of microwave.